2013
DOI: 10.1186/1471-2407-13-530
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy versus radical prostatectomy in patients with localized prostate cancer: long-term follow-up

Abstract: BackgroundThe objective of this work was to assess the overall survival, cause-specific survival and biochemical failure-free survival of a contemporary cohort of patients with localized prostate cancer (PCa) treated with intensity-modulated radiation therapy (IMRT) or radical prostatectomy (RP).MethodsWe did a retrospective cohort study of our institution’s registry of patients undergoing either IMRT or RP between January 1999 and March 2010, and assessed Prostate Specific Antigen (PSA), age at diagnosis, Gle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 24 publications
4
28
0
1
Order By: Relevance
“…Our results show that the radical radiotherapy treatment results of early prostate cancer are excellent. Overall the 5year OS (88.9%), PCSS (97.9%), MFS (94.8%) and BRFS (88.7%) were similar or better compared with the figures reported in other studies [12][13][14][15][16][17][18]. In recent years, there have been some large high-quality population-based studies that have demonstrated an association between increased overall mortality and comorbidity [19][20][21].…”
Section: Discussionsupporting
confidence: 65%
“…Our results show that the radical radiotherapy treatment results of early prostate cancer are excellent. Overall the 5year OS (88.9%), PCSS (97.9%), MFS (94.8%) and BRFS (88.7%) were similar or better compared with the figures reported in other studies [12][13][14][15][16][17][18]. In recent years, there have been some large high-quality population-based studies that have demonstrated an association between increased overall mortality and comorbidity [19][20][21].…”
Section: Discussionsupporting
confidence: 65%
“…Thus again, our data substantially indicate that SC in patients with RT only is related to a strong selection bias rather than indicating a real risk of SC after RT. Mainly patients being not fit for surgery will be selected for RT with smoking related disorders and age being major reasons [30, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarizes the PCSM rates for patients with highrisk PC from previous reports. (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(38)(39)(40) The 10-year PCSM rates after RP and EBRT including IMRT were 5-9% (7-11) and 8-12%, (13,39) respectively. The PCSM rate after CIRT (Figs S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…(6) In contrast, favorable treatment outcomes after RP have been demonstrated, (7)(8)(9)(10)(11) and the superiority of RP compared with EBRT, including intensity modulated RT (IMRT) with or without ADT, has been suggested by several authors. (12)(13)(14)(15)(16) In addition, high-dose or low-dose-rate brachytherapy combined with EBRT plus ADT is sometimes selected for patients with high-risk PC. (17,18) However, to the best of our knowledge, the best treatment for high-risk PC is still unknown, because no adequate comparisons of treatment modalities for high-risk PC have been performed.The National Institute of Radiological Science (NIRS) started carbon-ion RT (CIRT) for localized PC in 1995.…”
mentioning
confidence: 99%